DEVELOPING EDUCATION SYSTEM OF PRESCHOOL CHILDREN - Abduramanova Diana Valeryevna, Abduramanova Diana Valeryevna (Журнал иностранных языков и лингвистики, 2021)
In the history of human learning (as in education) arose from the need to preserve and pass on available experience to the younger generation, preparing it, so for independent living. In recent years, the teaching language is increasingly included the concept of "teaching education"; "Educate training", emphasizes the unity of education and training of personality formation.